An Assessment of Life Cycle Greenhouse Gas Emissions for day spa services in Eastern Thailand: A Case Study in Chonburi, Rayong, and Trad Provinces - Ukaew, Suchada; Tungtakanpoung, Dondej; Chongsithiphol, Srisuda (Naresuan University Journal: Science and Technology (NUJST); Vol 28 No 1 (2020): January - March 2020, 2020)
Day spa services have become increasingly popular as people have become more interested in health and wellness due to a rapid increase in the older population, and also because the travel and tourism sectors are constantly offering these services. We conducted research to evaluate greenhouse gas (GHG) emissions of day spa services from twelve spas in three Eastern provinces in Thailand: Chonburi, Rayong, and Trad. The system boundary was from cradle to grave, starting from raw material acquisition, progressing to the spa service, and finishing with the waste disposal stage. The functional unit was one body spa package per person. The results showed that day spa services had GHG emissions of 5.76 kg CO 2 eq/person (ranging from 3.54 to 9.69 kg CO 2 eq/person). The net GHG emissions for each stage of the day spa services were as follows: service (84.70%), laundry (9.27%), waste disposal (5.82%) and transportation (0.22%). The service stage had the highest impact on overall GHG emissions, mostly due to electricity consumption from air conditioners and electrical equipment. Possible ways to reduce this service electricity usage included maintaining the air conditioners regularly, installing insulation in ceilings and walls, producing hot water either from solar or air conditioner sources, replacing incandescent bulbs with LED ones, and planting trees around the buildings. In addition, application of the 3R concept, (reduce, reuse and recycle), in the use of materials may not only help mitigate the emissions, but also minimize waste disposal, landfill, and the cost of excess resources used by day spa services.   Keywords: Life cycle assessment, Greenhouse gas emissions, Day spa, Spa service, Thailand